How banks create gridlock to save liquidity in Canada's large value payment system - Rod Garratt; Zhentong Lu; Phoebe Tian (Bank of Canada, 2023)
Using detailed data from Canada's new high-value payment system (HVPS), we show how participants of the system save liquidity by exploiting the new gridlock resolution arrangement. These observed behaviors are consistent with the equilibrium of a "gridlock game" that captures the key incentives that participants face in the system. The findings have important implications for the design of HVPSs and shed light on financial institutions' liquidity preference.
Keywords: E42; E58; G21; 330; Financial institutions; Payment clearing and settlement systems